COMBO-FISH: specific labeling of nondenatured chromatin targets by computer-selected DNA oligonucleotide probe combinations. (September 2003) - Hausmann, Michael; Winkler, Ralph; Hildenbrand, Georg; Finsterle, Jutta; Weisel, Andrea; Rapp, Alexander; Schmitt, Eberhard; Janz, Siegfried; Cremer, Christoph
Here we present the principle of fluorescence in situ hybridization (FISH) with combinatorial oligonucleotide (COMBO) probes as a new approach for the specific labeling of genomic sites. COMBO-FISH takes advantage of homopurine/homopyrimidine oligonucleotides that form triple helices with intact duplex genomic DNA, without the need for prior denaturation of the target sequence that is usually applied for probe binding in standard FISH protocols. An analysis of human genome databases has shown that homopurine/homopyrimidine sequences longer than 14 bp are nearly homogeneously distributed over the genome, and they represent from 1% to 2% of the entire genome. Because the observation volume in a confocal laser-scanning microscope equipped with a high numerical aperture lens typically corresponds to an approximate 250-kb chromatin domain in a normal mammalian cell nucleus, this volume should contain 150–200 homopurine/homopyrimidine stretches. Using DNA database information, one can configure a set of distinct, uniformly labeled oligonucleotide probes from these stretches that is expected to exclusively co-localize within a 250-kb chromatin domain. Due to the diffraction-limited resolution of a microscope, the fluorescence signals of the configured oligonucleotide probe set merge into a typical, nearly homogeneous FISH spot. Using a set of 32 homopyrimidine probes, we performed experiments in the Abelson murine leukemia region of human chromosome 9 as some of the very first proofs-of-principle of COMBO-FISH. Although the experimental protocol currently contains several steps that are incompatible with living cell conditions, the theoretical approach may be the first methodological advance toward the long-term but still elusive goal of carrying out specific FISH in high-resolution fluorescence microscopy of vital cells.